Pengaruh Biaya Operasional dan Biaya Promosi terhadap Penjualan Sepeda Motor Honda PCX di PT. Daya Anugerah Mandiri Purwakarta Periode Tahun 2016-2020 - Abdul Kudus; De Santika Septiana (Journal on Education, 2023)
This study was conducted to determine whether there is an effect of operational costs and promotional costs on sales, the data source taken is the primary data source, the data source is directly given to data collectors. This type of research method is an associative method with a quantitative approach the explains the causal relationship and influence between variables through hypothesis testing. The data analysis method used in this study is multiple linear regression with the help of SPPS software version 21. The result of this study indicate that operational costs and promotional cost have no significant effect on sales with finning value nilai Fvalue 13,584 < Ftable 19,000 tingkat signifikasi 0,069 > 0,05.